WASTE LEMON PEEL AS A CIRCULAR SOLUTION FOR THE REMEDIATION OF LEAD-CONTAMINATED SLUDGE FOR LAND APPLICATION - Duru, Chinonye; Ibrahim, Fatima Badiru; Dandajeh, Aliyu Adamu (FUDMA JOURNAL OF SCIENCES, 2023)
Lead-contaminated sludge is a major environmental concern, as land application of this material can contaminate surfaces with toxic heavy metals. To address this, a novel approach to utilizing waste lemon peel (WLP) for the remediation of lead-contaminated sludge for land application with the circular economy in perspective is presented. The WLP was collected from local producers and characterized using Fourier transform infrared (FTIR) spectroscopy to determine the functional groups present. The hydroxyl, carboxyl, ether, and amide groups are the main functional groups in the sample and they have been identified as potential sites responsible for binding heavy metal ions to the biomass.The sludge samples were collected from the Ahmadu Bello University Water treatment plant and analyzed for contamination. The effects of WLP on the lead sorption were investigated using batch experiments. The results indicated that lead sorption onto the WLP was significantly as high as 90.5%. The WLP was found to effectively reduce the lead from the contaminated sludge. This study aimed to identify the capability of WLP as a low-cost and sustainable material for the remediation of lead-contaminated sludge for land application, indicating the potential for waste materials to be utilized in the circular economy. The Material Circularity Indicator of 0.835 indicated a highly circular system.